Ag-nanoparticle as a Q switched device for tunable C-band fiber laser - Ahmad, Harith; Ruslan, N.E.; Ali, Z.A.; Reduan, S.A.; Lee, C.S.J.; Shaharuddin, R.A.; Nayan, N.; Ismail, Mohd Afiq (Elsevier, 2016)
The use of silver (Ag)-nanoparticle as saturable absorber (SA) to induce tunable Q-switched fiber laser in C-band is demonstrated. The Ag-nanoparticle SA exhibits modulation depth of 31.6% and saturation intensity of 0.54 MW cm−2. The SA is integrated into the laser cavity by sandwiching it between two fiber ferrules. Lasing in CW region starts at 10 mW, whereas stable self-starting Q-switching with a central wavelength of 1558.4 nm begins at 20 mW. As the pump power increases, the repetition rate varies from 10.5 kHz to 24.4 kHz and the narrowest pulse width obtained is around 6.5 µs. The Q-switched laser has a tuning range of 27.3 nm (1552.9–1580.2 nm). The stability of the pulse is verified from the radio-freqeuncy (RF) spectrum with a measured signal-to-noise ratio (SNR) of 46.22 dB. The ability of Ag-nanoparticle as an effective SA may lead to further development of pulsed fiber laser in the field of photonics.